Environmental risks for application of magnesium slag to soils in China - Xiao-bin WANG; Xiang YAN; Xiu-ying LI (Journal of Integrative Agriculture, 2020)
Magnesium slag (MS) is one of the main industrial solid wastes produced by the magnesium industry. Solving the problem of its disposal has attracted much attention with increasing amounts of solid wastes generated in the production of metallic magnesium. Because MS contains calcium (Ca), magnesium (Mg), and silicon (Si), some have tried to use MS as Si-Ca-Mg fertilizer or for soil amendment in agriculture. However, in the magnesium metallurgical process, some pollutant elements are introduced into MS, resulting in the enrichment of these pollutants in MS, such as arsenic (As), chromium (Cr), cadmium (Cd), mercury (Hg), copper (Cu), nickel (Ni), fluorine (F) and chlorine (Cl). Research indicates that the enrichment of these pollutants can result in high levels, especially for Cd, Hg, Cu, Ni, F and Cl (0–4, 0–0.74, 20–127, 100–170, 2 277–14 800 and 133–1 000 mg kg−1, respectively) in some MS in China. These levels are often far beyond the limits (≤0.3, ≤0.5, ≤50 and ≤60 mg kg−1 for Cd, Hg, Cu and Ni, respectively) of the Chinese Risk Screening Values for Soil Contamination of Agricultural Land based on the Soil Environmental Quality Risk Control Standard for Soil Contamination of Agricultural Land (GB 15618-2018) or the critical reference values (≤800 and ≤200 for F and Cl, respectively). The elements Hg, Cu, Cr and F (detected in MS leachate at 0.00023–0.0052, 0.043–3.89, 0.026–0.171, and 1.43–8.52 mg L−1, respectively) also exceed the limits (Class IV–V) of the Chinese Standard for Groundwater Quality (GB/T 14848-2017). Based on the above results, it is suggested that without any pretreatment for reducing harmful pollutants MS should not be allowed to be applied for soil remediation or conditioning directly into farmlands in order to ensure soil health, food safety and environmental quality.